O uso do instagram como ferramenta de ensino-aprendizagem relacionada à saúde sexual e reprodutiva de adolescentes escolares. - Farias, Thiago Rodrigo Cruz (2024)
Nowadays, the growing immersion in apps and digital social networking sites has reinvented the processes of social interaction, fostering the fertilization of new reading practices and (re)defining the way knowledge is disseminated. In this context, we highlight the online social network Instagram, which has emerged in this virtual space with a view to becoming a disseminator of new forms of collaborative encounters on the web, as it presents itself as an online social network focused on communication and visual authorship, where teenagers have a profile and use it frequently. Objectives: Evaluate the use of Instagram as an educational technology in the sexual and reproductive health of school adolescents. Methodology: Intervention study, longitudinal and with a quantitative and qualitative approach, carried out from October to December 2023 with 366 adolescents from the State Professional High School, located in the municipality of Santa Quitéria-CE, where in the first stage a sociodemographic questionnaire and the Pre-test Scale of Self-efficacy in Condom Use were applied, the second stage consisted of planning and developing an educational intervention on sexual and reproductive health with 50 first-year students, using the social network Instagram, and the third stage involved applying the Final Evaluation Questionnaire and post-testing the Self-Efficacy Scale for Condom Use among Adolescents. Results: A profile was created on the Instagram social network entitled, @proj.saudesexualnaadolescencia, designed for educational interaction on sexual and reproductive health, producing interactive posts for 07 weeks. 45 posts, 18 polls, 171 stores, 599 comments, 04 reels and 01 closing live were produced. The result of the post-test of the Condom Use Self-Efficacy Scale showed a statistically significant difference (p<0.05) in the skill dimension. Conclusion: Instagram has made it possible to be an online learning environment, focused on teaching with successful pedagogical actions based on the analysis of the good engagement of students with the content published.